Pengaruh Budaya Indonesia Dalam Pembelajaran Di Sekolah Indonesia Kuala Lumpur - Maulida, Roichanatul; Nadiya, Dwi Zuyyina; Annisa, Khoiridatun; Dewi, Yuyun Kusuma; Ahsani, Eva Luthfi Fakhru (Metodik Didaktik, 2021)
This study aims to determine the influence of Indonesian culture on the Kuala Lumpur Indonesian School. The method used in this research is qualitative. Data collection techniques, namely interviews and documentation. The data analysis technique used is descriptive analytic method, by describing the data with words, pictures, and not numbers. The results showed that the Kuala Lumpur Indonesian School was able to introduce Indonesian culture in Malaysia through learning activities, extracurricular activities, and performing arts, so that students could preserve Indonesian culture. Indonesian culture can be taught through educational facilities, through educational facilities it can introduce the existing culture in Indonesia to students from an early age, so that students know the various cultures that exist in Indonesia. With this activity, students of the Kuala Lumpur Indonesian School can find out and preserve Indonesian culture on the international stage.